The Correlation Between House Environment Factor and Incidence of Pneumonia on Children under Five Years Old in West Java (Data Analysis of the Indonesian Demographic and Health Survey 2017) - Rinda Tri Nugraheni; Laila Fitria (JUMP Health (Journal of Ultimate Public Health), 2020)
Pneumonia is one of the most common causes of child mortality in Indonesia. The prevalence of pneumonia in children under five in the last five years has increased by 1,6% in 2013 to 2% in 2018. West Java Province is the fourth highest prevalence of pneumonia on children under five in Indonesia. The aim of the study was to analyze the factors associated with the incidence of pneumonia in children under five in West Java Province. The study was conducted with a cross sectional design using secondary data on the Indonesian Demographic and Health Survey 2017. Dependent variable of this study was pneumonia among children aged 12-59 months. Meanwhile, independent variables are house environment factors, children characteristic factors, and economic factors. The data analysis used in this study is Chi-Square test. The results indicated that there was a significant correlation between low wealth index (OR = 4,23; 95% CI: 1,72-10,41), type of residence (OR = 3,70; 95% CI: 1,71-8,02), and type of wall (OR = 4,84; 95% CI: 1,55-15,14) with pneumonia on children under five years old.